The perceived psychological distance of climate change impacts and its influence on support for adaptation policy. Issue 73 (July 2017) - Singh, Ajay S.; Zwickle, Adam; Bruskotter, Jeremy T.; Wilson, Robyn
Abstract: Factors influencing support for climate mitigation policy in the United States are well researched, however, research regarding individuals' support for climate adaptation policy is relatively sparse. This study explores how an individual's perception of climate change impacts may influence their support for adaptation actions. Results of a survey of the U.S. public (n = 653) indicates that individuals who believe climate change impacts are unlikely to happen or will primarily affect other people in other places are less likely to be concerned about climate change impacts and less likely to support climate adaptation. However, an individual's support for climate change adaptation measures is not influenced by their perception of when climate change impacts will occur even when taking into account concern for climate impacts. Critical for policy-makers, a belief that climate adaptation measures will not be effective attenuates the relationship between psychological distance, concern for climate change impacts, and adaptation policy measures. Our results indicate that to effectively communicate about climate change, policy-makers should emphasize that: (i) climate change impacts are occurring, (ii) that their constituents are being affected now, or will be in the future, and (iii) communicate that adaptation measures can be effective in addressing risks associated with climate change impacts.